2024
DOI: 10.1002/hsr2.1957
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of Vernal Keratoconjunctivitis among a Ghanaian clinical cohort: A case‐control study

Samuel Kyei,
Mary Nkansah,
Kofi Asiedu
et al.

Abstract: BackgroundVernal Keratoconjunctivitis (VKC) has been determined to be highly prevalent in countries within the tropical climate region. However, little evidence from studies conducted within this region has been put forward to support this claim.AimTo determine the prevalence and risk factors of VKC among a Ghanaian clinical cohort.MethodsA 3‐year case‐control study was conducted in a tertiary eye care institution, and medical records of patients who had been diagnosed of VKC between 2018 and 2021 were reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Additionally, corneal opacity and ulceration contributed to decreased visual acuity as part of the vicious cycle. A study conducted in the general population concluded that VKC is common among youngsters and is frequently related with atopic comorbidities [11] . As a result of our country's limited resources and disastrous war, most patients are unable to access health-care facilities.…”
Section: Table 1: Distribution Of the Cases By Sex Age Age Of Onset R...mentioning
confidence: 99%
“…Additionally, corneal opacity and ulceration contributed to decreased visual acuity as part of the vicious cycle. A study conducted in the general population concluded that VKC is common among youngsters and is frequently related with atopic comorbidities [11] . As a result of our country's limited resources and disastrous war, most patients are unable to access health-care facilities.…”
Section: Table 1: Distribution Of the Cases By Sex Age Age Of Onset R...mentioning
confidence: 99%